Tegnologiese innovasie en Suid-Afrika - Mulder, F. Shylock (Scientia Militaria - South African Journal of Military Studies, 2012)
The article below deals with technological developments in the Republic of South Africa necessitated by the arms boycotts engineered against the Republic by the United Nations Organisation. The writer of the article stresses the need for co ordination and sinchronlzation of research and development in the field of technology in South Africa especially with regard to priorities and effort. "A new form of Military Technological Strategy - each side is merely trying to outdo in performance the equipment of the other side - its object is to make them functionally obsolete -" Andre Beaufré